Imaging approach to unifocal sclerotic bone lesions – A pictorial essay - Kakarla S (Journal of Medical and Scientific Research, 2020)
Sclerotic bone lesions are occasionally encountered in routine practice a few of which may not be clinically significant. Whenever a single focus is noted, it is mandatory to examine the entire skeleton to rule out concomitant lesions by way of limited skeletal survey or radionuclide bone scan. The etiological factors of unifocal sclerotic bone lesions are many. The aim of this essay is to identify the lesions and to find out the etiology and to arrive at a final diagnosis. The sclerotic lesions include developmental/congenital, post traumatic, inflammatory, infective, metabolic, hemopoietic, neoplastic, and miscellaneous groups. The radiological characteristics are described in detail so that a final diagnosis can be made. Often, conventional radiology is adequate but CT/MRI may be helpful. The final diagnosis rests on histopathology.